2019
DOI: 10.1002/2211-5463.12706
|View full text |Cite
|
Sign up to set email alerts
|

Proximity labeling to detect RNA–protein interactions in live cells

Abstract: RNA biology is orchestrated by the dynamic interactions of RNAs and RNA‐binding proteins (RBPs). In the present study, we describe a new method of proximity‐dependent protein labeling to detect RNA–protein interactions [RNA‐bound protein proximity labeling (RBPL)]. We selected the well‐studied RNA‐binding protein PUF to examine the current proximity labeling enzymes birA* and APEX2. A new version of birA*, BASU, was used to validate that the PUF protein binds its RNA motif. We further optimized the RBPL labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Substitution of the described methodologies by other technologies to frame these interactions is thus desirable. Interestingly, BASU was recently reported to capture RNA-protein interactions using labeling times as short as 1 min [123].…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the described methodologies by other technologies to frame these interactions is thus desirable. Interestingly, BASU was recently reported to capture RNA-protein interactions using labeling times as short as 1 min [123].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the fast labeling time of APEX has been leveraged to identify dynamic changes in protein complex composition (Lobingier et al, 2017; Paek et al, 2017). APEX has also been used for identification of proteins interacting with specific sequences of RNA (Kaewsapsak, Shechner, Mallard, Rinn, & Ting, 2017; Lu & Wei, 2019; Ramanathan et al, 2018) and DNA (Gao et al, 2018; Myers et al, 2018; Qiu et al, 2019). Finally, we note that APEX has recently been used to directly label and identify RNAs (Fazal et al, 2019; Padron, Iwasaki, Ingolia, & Proximity, 2019; Zhou et al, 2019).…”
Section: Apex‐based Proximity Labelingmentioning
confidence: 99%
“…Its co-expression with a fusion of the BoxB recognizing λ N-peptide and BirA* or BASU allows the biotinylation of proteins bound to or associated with the flanked RNA sequences. RaPID was used to identify proteins that bind to known RNA motifs (e.g., the IRE, TNF-CDE, or PUF RNA motifs [ 64 , 101 ]) and to analyze how mutant RNA motifs affect protein binding. Additionally, by probing the interactome of untranslated regions of the Zika virus genome, an RBP (QKI) that is highly expressed in neuronal progenitor cells was identified as a candidate host protein essential for the Zika virus replication [ 64 ].…”
Section: Proximity Labeling Of Rna–protein Interactions: Finding the Protein Partnersmentioning
confidence: 99%
“…Moreover, the authors suggest performing subsequent analysis like comparison of identified proteins with those reported in the Contamination Repository for Affinity Purification (CRAPome; [ 102 ]). Although transient expression of the BASU-λ N-peptide fusion was sufficient for identifying specifically associated proteins for Zika virus, other studies suggest stable genomic integration of the labeling enzyme to increase the signal-to-noise ratio [ 101 ]. A potential drawback of the current version of RaPID is that the tagged RNAs are not expressed under their native conditions and therefore are not studied at their physiological concentrations.…”
Section: Proximity Labeling Of Rna–protein Interactions: Finding the Protein Partnersmentioning
confidence: 99%